THE RATIONAL ACTOR MODEL ANALYSIS OF DONALD TRUMP’S PERCEPTION TOWARDS THE TRAVEL BAN POLICY - Maharani Putri; Mohamad Dziqie Aulia Al Farauqi; Khoirul Amin (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
The United States is one of the countries that immigrants move to. The economic, political, and social aspects are one of the reasons why the migration process occurs. Although the arrival of immigrants has become part of the development of the United States, the large number of immigrants entering has caused problems so that the Travel Ban policy was formed to protect the interests of its citizens from immigrant threats. Using a descriptive qualitative approach, this research aims to describe how Donald Trump's perception in making the Travel Ban policy. Through the decision-making theory of the rational actor model, the results show that the views on immigrants and the political environment influence Donald Trump as a main actor in his decision-making process. Thus, through the calculation of profit and loss, making the Travel Ban policy is considered a rational and profitable choice for his country.